(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The article presents theoretical considerations concerning the relationship between the original text and the texts of translations with the use of the cognitive categorization model. From the perspective of the theory of prototypes, translation studies can be conducted at the general level of texts: the source and the target and at the detailed level: translation units and their translation equivalents. The structure of a category will depend on the researcher’s intuition and their decision to choose the unit in the center of the category under consideration. The aim of the paper is to propose several new categorization models, reflecting the various possibilities of building a category of translations with a central-peripheral structure at the level of the texts as a whole. This is due to the consideration of whether and in what sense the original text can be perceived as a prototype in relation to the translation text? In the center of the translation category, it is possible, for example, to place an ideal translation of the original, potential or actually existing in the host culture. The central-peripheral structure of translation category may also be useful in presenting the results of the translator’s decision-making process regarding the selection of a translation equivalent, as well as in the process of critical analysis of various translation solutions, especially in translation series, which, however, is beyond the scope of the present article.